Unilateral angioedema of tongue following ginseng containing multivitamin intake in patient with SLE: a case report - Pant, Manish Nath; Thapa, Ashish (Journal of General Practice and Emergency Medicine of Nepal, 2020)
Unilateral angioedema of tongue is a rare presentation of allergic reaction. If not identified and treated immediately, may lead to compromise of the airway and warrant tracheostomy or sometimes may also lead to death. In lupus patients, angioedema may be due to an acquired type of C1 inhibitor deficiency. Acquired angioedema can also be drug induced mostly seen with the use of non-steroidal anti-inflammatory drugs, contrast media, proton pump inhibitors and serotonin reuptake inhibitors. There are rare cases reported of angioedema related to Ginseng intake.